Work Motivation and Psychological Well-Being on Teacher Performance at Perguruan Alkhairaat, Palu, Indonesia - Muhammad Muhammad; Achmad Syahid (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
The UNESCO ranking (2016) and BAN S/M accreditation data show that the quality of Indonesian education is still low, and this is triggered by the quality of its teachers. It is predictable that approximately 1500 schools and 70 thousand teachers owned by Perguruan Alkhairaat in Palu, Central Sulawesi, Indonesia, also play an important role in the education process, especially in Central and Eastern Indonesia. The study aims to prove the influence of work motivation and psychological well-being on the performance of teacher at Perguruan Alkhairaat. This study uses a quantitative approach with 210 teachers. The sampling technique used is a non-probability sampling technique, namely accidental sampling. The teacher’s performance measurement tool uses the Teacher’s Job Performance Self-Rating Questionnaire (TJPSQ) developed by Amin et al. (2013), the work motivation measurement tool uses The Motivation for Teaching Scale developed by Abos et al. (2018), while the psychological measurement tool well-being using Psychological Well-Being Scales (PWBS) developed by Ryff (1989). The result of the research significance value is .000 (P < .05) meaning there is a significant influence between work motivation and psychological well-being on the performance of teacher at Perguruan Alkhairaat. The results of the regression analysis test showed that R Square .282 or 28.2% showed the large influence of work motivation and psychological well-being on the teacher performance at Perguruan Alkhairaat.